2022
DOI: 10.1039/d1na00880c
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanostructured materials and their potential applications: progress, challenges and perspectives

Abstract: Extensive research in nanotechnology has been going on to investigate new behaviours and properties of materials with nanoscale dimensions. ZnO NPs owing to their distinct physical and chemical properties have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(156 citation statements)
references
References 292 publications
4
100
0
Order By: Relevance
“…ZnO is classified as active photocatalysts due to wide absorption range and high photostability (Kołodziejczak-Radzimska and Jesionowski, 2014;Laurenti et al, 2017). Besides, ZnO is harmless and inexpensive, and ZnO nanostructures can be synthesized via different methods (Khan et al, 2019a(Khan et al, , 2019bRaha and Ahmaruzzaman, 2022). Qi et al (Qi et al, 2017) reviewed the photocatalytic applications of ZnO and suggested that the photocatalytic performance of ZnO nanomaterials could be improved by: 1) doping with metals or non-metals, 2) constructing heterojunctions, 3) coupling with carbon nanostructures, or 4) deposition of noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is classified as active photocatalysts due to wide absorption range and high photostability (Kołodziejczak-Radzimska and Jesionowski, 2014;Laurenti et al, 2017). Besides, ZnO is harmless and inexpensive, and ZnO nanostructures can be synthesized via different methods (Khan et al, 2019a(Khan et al, , 2019bRaha and Ahmaruzzaman, 2022). Qi et al (Qi et al, 2017) reviewed the photocatalytic applications of ZnO and suggested that the photocatalytic performance of ZnO nanomaterials could be improved by: 1) doping with metals or non-metals, 2) constructing heterojunctions, 3) coupling with carbon nanostructures, or 4) deposition of noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is one of the most popular semiconducting materials with a wide energy bandgap of 3.37 eV and a large exciton binding energy of 60 meV [1]. Especially, hierarchical ZnO nanostructure has been a useful material with various applications in the field of energy production, such as photoelectrochemical water splitting to produce hydrogen fuel [2] and dye-sensitized solar-cell [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] ZnO has thus been the champion material for UV detection with extensive research over time. 27,[37][38][39][40][41][42][43][44] Nevertheless, ZnO has had a lot of hidden surprises under its hat, which continue to be revealed to researchers. One such example of this is its ability to detect UV without providing any external electrical bias, in so called self-powered PDs.…”
Section: Introductionmentioning
confidence: 99%